THE IMPACT OF SHIPPING ACCIDENTS ON MARINE ENVIRONMENT: A STUDY OF TURKISH SEAS - Ceyhun, Gokce Cicek (European Scientific Journal, ESJ, 2014)
Shipping accidents are unexpected events that result in financial loss and properties, damages and either loss of people. Several reasons as human errors, technical failures, natural conditions, shipping factors, route conditions and cargo related factors play role in these accidents. Unfortunately, shipping accidents are inevitable cases of maritime field, in contravention of creative and innovative technologies in shipping sector and execution of precautionary safety rules and regulations. Main purpose of this paper is to investigate the effects of shipping accidents on marine environment in Turkish Seas. Within this scope firstly, the literature related shipping accidents and marine environment were handled. Then, the statistics of shipping accidents and marine environment in Turkish Seas were analyzed. Finally, future projections were provided in the light of presented matters and current developments.